The enantioselective potential of amylose tris(3‑chloro-5-methylphenyl carbamate)-based chiral stationary phase in sub/supercritical fluid and normal phase liquid chromatography - Denisa Folprechtová; Patricia Maestro Martínez; Květa Kalíková (Journal of Chromatography Open, 2024)
The enantioselective potential of amylose tris (3‑chloro-5-methylphenylcarbamate) based chiral stationary phase in sub/supercritical fluid chromatography and normal phase liquid chromatography was evaluated. To test its enantioselective potential the enantiomeric resolution of a set of nineteen important chiral biologically active compounds was explored. The influence of the cosolvent and different mobile phase additives on the retention, enantioselectivity, and enantioresolution was investigated. The type, as well as the amount of cosolvent used in the mobile phase, are critical for enantioseparation efficiency in both techniques. Using basic or mixed additives in the mobile phases significantly improved enantioseparation and peak shape of different compounds, especially β-blockers. Results showed the high enantioselective potential of the chlorinated amylose-based chiral stationary phase in both chromatographic techniques with overall higher enantiorecognition ability in sub/supercritical fluid chromatography.